Fibroblast Growth Factor 23 and Klotho Are Associated With Trabecular Bone Score but Not Bone Mineral Density in the Early Stages of Chronic Kidney Disease: Results of the Cross-Sectional Study - Kužmová, Z; Kužma, M; Gažová, A; Kovářová, M; Jackuliak, P; Killinger, Z; Kyselovič, J; Payer, J (Physiological research, 2021)
This study evaluates bone mineral density (BMD) and trabecular bone score (TBS) in relationship with new markers of chronic kidney disease (CKD), fibroblast growth factor 23 (FGF23), and klotho. The patients in this cross-sectional study were divided as follows: group A -patients in stages G1-3; group B -patients in stages G4 - 5 according to KDIGO. Plasma levels of soluble klotho and FGF23 were determined by ELISA. Bone mineral density (BMD) and trabecular bone score (TBS) were measured. 74 patients with CKD (mean age 68.8 years) were included in the study. Higher levels of FGF23 were observed in group B (N=15) compared to group A (N=59; p=0.001) were observed. FGF23 was higher in group A compared to group B. Significant difference in TBS within the first 3 stages of CKD was observed (mean TBS in G1=1.375 vs. G2=1.340 vs. G3a=1.24; p<0.05) and negative correlation of FGF23 and TBS (R=-0.33; p=0.05) and positive correlation between klotho and TBS (R=0.419; p=0.04) was observed. This study confirmed that FGF23 and klotho are associated with TBS, but TBS reflects a decrease in kidney function only in the first 3 stages of CKD. Thus, FGF23 and klotho together with TBS are promising markers of early trabecular bone impairment in CKD.
Keywords: Klotho Proteins; Humans; Fibroblast Growth Factor-23; lidé středního věku; trabekulární kostní tkáň; Female; Aged; senioři; lidé; Biomarkers; chronická renální insuficience; biologické markery; ženské pohlaví; stupeň závažnosti nemoci; Male; Middle Aged; Bone Density; Aged, 80 and over; kostní denzita; Cross-Sectional Studies; Severity of Illness Index; fibroblastový růstový faktor 23; senioři nad 80 let; Cancellous Bone; proteiny Klotho; mužské pohlaví; Renal Insufficiency, Chronic; průřezové studie